Electroencephalography in Assessment of Autism Spectrum Disorders: A Review - Milovanovic, Maja; Grujicic, Roberto (Frontiers in Psychiatry, 2021)
Electroencephalography (EEG) can further our understanding of autistic spectrum disorders (ASD) neurophysiology. Epilepsy and ASD comorbidity range between 1.8-60%, but its temporal relationship, causal mechanisms, and interplay with intellectual disability are still unknown. Epileptiform discharges with or without seizures go as high as 60%, and associate with epileptic encephalopathies, a conceptual term suggesting that epileptic activity can lead to cognitive and behavioral impairment beyond the underlying pathology. Seizures and ASD may reflect outcomes from common processes, such as defects in GABAergic fibers or in GABA receptor function. Several genetic syndromes and variants that cause such dysregulation leads to epilepsy and ASD. Likewise, primary epilepsy may impact synaptic plasticity and cortical connectivity, which, in turn, may predispose a developing brain to cognitive delays and behavioral impairments. The quantitative EEG techniques could be a useful tool in detecting and possibly measuring dysfunctions in specific brain regions and neuronal regulation in ASD. Power spectra analysis suggests a U-shaped pattern of power abnormalities, with excessive power in low-frequency and high-frequency bands. These may result from a complex pattern of neurochemical alterations that affect the physiology of inhibitory GABAergic interneurons and their modulation of excitatory activity in pyramidal cells. Functional connectivity between different brain regions via EEG coherence studies showed overall local over-connectivity and long-range under-connectivity. Recent advances in quantitative EEG analytic methodology and well-known epilepsy ASD co-morbidity consistently indicate a role of aberrant GABAergic transmission that has consequences on neuronal organization and connectivity, especially in the frontal cortex.